SUMBER PENGETAHUAN MENURUT FILSAFAT ADVAITA VEDANTA - Wayan Ngurah Eka Kurniawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
Humans have a very large curiosity that is very difficult to satisfy. As stated by Maslow, this dissatisfaction is partly because humans have needs that are hierarchically increasing in line with the achievement of lower needs, they will try or desire to achieve other higher needs. To satisfy their curiosity, humans make efforts, both consciously and sometimes unconsciously. Human efforts to fulfill this curiosity then produce two types of knowledge, namely ordinary knowledge and scientific knowledge. In writing this article the method used is qualitative method, using qualitative descriptive analysis. Furthermore, in analyzing the research data, the authors carried out a series of stages so that the results of this study were logical, objective and empirical. The series of stages are reducing data, displaying data, verifying data and interpreting research data. According to Advaita Vedanta, human knowledge is the result of a combination of sensory data obtained through the Pratyaksa Pramana method with ideas in the mind in the form of memory which are processed, analyzed or synthesized following the Anumana Pramana and Upamana Pramana methods, and can even be equipped with with the Pramana Word method, Arthapatti and Anupalabdi. Keywords: Humans, Knowledge, Scientific